A pilot feasibility randomized controlled trial on combining mind-body physical exercise, cognitive training, and nurse-led risk factor modification to reduce cognitive decline among older adults with mild cognitive impairment in primary care - Zijun Xu; Dexing Zhang; Allen Lee; Regina Wing Shan Sit; Carmen Wong; Kam-Pui Lee; Benjamin Hon Kei Yip; Jennifer Y. S. Tiu; Linda Lam; Samuel Yeung Shan Wong (2020)
To examine the feasibility and preliminary effectiveness of (1) combining cognitive training, mind-body physical exercise, and nurse-led risk factor modification (CPR), (2) nurse-led risk factor modification (RFM), and (3) health advice (HA) on reducing cognitive decline among older adults with mild cognitive impairment (MCI).It was a 3-arm open-labeled pilot randomized controlled trial in the primary care setting in Hong Kong. Nineteen older adults with MCI were randomized to either CPR (n = 6), RFM (n = 7), or HA (n = 6) for 6 months. The primary outcome was the feasibility of the study. Secondary outcomes included the Alzheimer's Disease Assessment Scale-Cognitive Subscale (ADAS-Cog), the Montreal Cognitive Assessment Hong Kong version (HK-MoCA), the Clinical Dementia Rating (CDR), the Disability Assessment for Dementia (DAD), quality of life, depression, anxiety, physical activity, health service utilization, and diet.Nineteen out the 98 potential patients were recruited, with a recruitment rate of 19% (95% CI [12-29]%, P = 0.243). The adherence rate of risk factor modification was 89% (95% CI [65-98]%, P = 0.139) for CPR group and 86% (95% CI [63-96]%, P = 0.182) for RFM group. In the CPR group, 53% (95% CI [36-70]%, P = 0.038) of the Tai Chi exercise sessions and 54% (95% CI [37-71]%, P = 0.051) of cognitive sessions were completed. The overall dropout rate was 11% (95% CI [2-34]%, P = 0.456). Significant within group changes were observed in HK-MoCA in RFM (4.50 ± 2.59, P = 0.008), cost of health service utilization in CPR (-4000, quartiles: -6800 to -200, P = 0.043), fish and seafood in HA (-1.10 ± 1.02, P = 0.047), and sugar in HA (2.69 ± 1.80, P = 0.015). Group × time interactions were noted on HK-MoCA favoring the RFM group (P = 0.000), DAD score favoring CPR group (P = 0.027), GAS-20 favoring CPR group (P = 0.026), number of servings of fish and seafood (P = 0.004), and sugar (P < 0.001) ate per day.In this pilot study, RFM and the multi-domain approach CPR were feasible and had preliminary beneficial effects in older adults with MCI in primary care setting in Hong Kong.Chinese Clinical Trial Registry (ChiCTR1800015324).